Activation of adenosine A2A or A2B receptors causes hypothermia in mice. (1st September 2018) - Carlin, Jesse Lea; Jain, Shalini; Duroux, Romain; Suresh, R. Rama; Xiao, Cuiying; Auchampach, John A.; Jacobson, Kenneth A.; Gavrilova, Oksana; Reitman, Marc L.
Abstract: Extracellular adenosine is a danger/injury signal that initiates protective physiology, such as hypothermia. Adenosine has been shown to trigger hypothermia via agonism at A1 and A3 adenosine receptors (A1 AR, A3 AR). Here, we find that adenosine continues to elicit hypothermia in mice null for A1 AR and A3 AR and investigated the effect of agonism at A2A AR or A2B AR. The poorly brain penetrant A2A AR agonists CGS-21680 and PSB-0777 caused hypothermia, which was not seen in mice lacking A2A AR. MRS7352, a likely non-brain penetrant A2A AR antagonist, inhibited PSB-0777 hypothermia. While vasodilation is probably a contributory mechanism, A2A AR agonism also caused hypometabolism, indicating that vasodilation is not the sole mechanism. The A2B AR agonist BAY60-6583 elicited hypothermia, which was lost in mice null for A2B AR. Low intracerebroventricular doses of BAY60-6583 also caused hypothermia, indicating a brain site of action, with neuronal activation in the preoptic area and paraventricular nucleus of the hypothalamus. Thus, agonism at any one of the canonical adenosine receptors, A1 AR, A2A AR, A2B AR, or A3 AR, can cause hypothermia. This four-fold redundancy in adenosine-mediated initiation of hypothermia may reflect the centrality of hypothermia as a protective response. Graphical abstract: Image 1 Highlights: Adenosine A2A agonists cause hypothermia via peripheral receptors. Adenosine A2B agonists cause hypothermia via central action. Adenosine A2B agonism activates preoptic area and paraventricular hypothalamic neurons.